2022
DOI: 10.3389/fnmol.2022.892820
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CACNA1I Cav3.3 Dysfunction in Hemiplegic Migraine

Abstract: Familial hemiplegic migraine (FHM) is a severe neurogenetic disorder for which three causal genes, CACNA1A, SCN1A, and ATP1A2, have been implicated. However, more than 80% of referred diagnostic cases of hemiplegic migraine (HM) are negative for exonic mutations in these known FHM genes, suggesting the involvement of other genes. Using whole-exome sequencing data from 187 mutation-negative HM cases, we identified rare variants in the CACNA1I gene encoding the T-type calcium channel Cav3.3. Burden testing of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Given that the R132H variant implicates the introduction of histidine within the extracellular end of the second transmembrane helix of Ca v 3.2, we assessed the effects of extracellular pH changes, alkalization (pH e 8.0) and acidification (pH e 6.5), on T-type currents. Consistent with previous results on T-type channels [11,12], extracellular alkalization and acidification produced a significant increase and decrease of the T-type current, respectively, in both Ca v 3.2 WT-and R132H-expressing cells (Fig. 1i, top panels).…”
supporting
confidence: 92%
“…Given that the R132H variant implicates the introduction of histidine within the extracellular end of the second transmembrane helix of Ca v 3.2, we assessed the effects of extracellular pH changes, alkalization (pH e 8.0) and acidification (pH e 6.5), on T-type currents. Consistent with previous results on T-type channels [11,12], extracellular alkalization and acidification produced a significant increase and decrease of the T-type current, respectively, in both Ca v 3.2 WT-and R132H-expressing cells (Fig. 1i, top panels).…”
supporting
confidence: 92%
“…Furthermore, CACNA1I and CACNA1H may be implicated in HM [39,125]. Patients with HM have been found to have an increased burden of missense variants in these two genes, further supporting the hypothesis that the genetic architecture of HM extends beyond the currently known genetic area for HM.…”
Section: Other Potential Genes Associated With Fhmmentioning
confidence: 73%
“…Adding to the complexity of understanding the interplay between the human genome and migraine development is the fact that the involvement of mutations in the three known FHM genes is not always established in patients with FHM; this supports the speculation that there might be unknown genes involved in FHM [38]. For example, a recent study found that genetic variants in the CACNA1I gene might contribute to the aetiology of HM [39]. A Danish study on FHM revealed that only 14% of the affected individuals had mutations in the three known genes.…”
Section: Fhm and The Three Known Genesmentioning
confidence: 95%
See 1 more Smart Citation